Substitution of fishmeal with soybean meal in humpback Grouper, Cromileptes altivelis juvenile diets supplemented with phytase - Rachman Syah; Usman Usman; Makmur Makmur; Taufik Ahmad (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Feeding experiments were conducted to evaluate the effects of replacing fishmeal with soybean meal in diet on growth of humpback grouper. Fifteen cages of 1 x 1 x 1.2 m3 each stocked with 16 humpback grouper juveniles (61.3 ± 0.4 g/pc) were set up randomly in seawater. Fish were fed to satiation twice daily for 112 days. The control diet contained 61.9% fishmeal (63.34% crude protein). Four isonitrogenous (48% crude protein) and isocaloric (4.7 kcal/g feed) diets supplemented with commercial phytase “Rhonozyme-P” at 0.075% were formulated to contain different levels (8%, 16%, 24%, and 32%) soybean meal (43.65% crude protein) as a partial replacement for fishmeal. These diets contained total phosphorus levels between 3.6—4.5 (±0.4) % and 0.7—1.5 (±0.04) % available phosphorus. Replacement of fishmeal with soybean meal (8 to 32% replacement) was not significantly different (P>0.05) to the control diet on daily growth rate (DGR), food conversion ratio (FCR), protein efficiency ratio (PER), and daily food consumption (DFC). However, the dietary levels of soybean meal significantly affected (P<0.05) whole body protein and phosphorus retention (Table 1). These data suggest that addition of phytase in diets could improve protein and phosphorus availability and reduce nitrogen and phosphorus loading in the environment. Phytase can therefore play an important role in formulating eco-friendly feed for humpback grouper. Based on P loading, supplementation of phytase enable up to 24% fishmeal replacement with soybean meal.